HIV Drug Resistance in Adults Receiving Early vs. Delayed Antiretroviral Therapy: HPTN 052 - Philip J. Palumbo (2018)
© 2017 Wolters Kluwer Health, Inc. All rights reserved. Introduction: We evaluated HIV drug resistance in adults who received early vs. delayed antiretroviral therapy (ART) in a multinational trial [HIV Prevention Trials Network (HPTN) 052, enrollment 2005-2010]. In HPTN 052, 1763 index participants were randomized to start ART at a CD4 cell count of 350-550 cells/mm 3 (early ART arm) or <250 cells/mm 3 (delayed ART arm). In May 2011, interim study results showed benefit of early ART, and all participants were offered ART regardless of CD4 cell count; the study ended in 2015. Methods: Virologic failure was defined as 2 consecutive viral loads >1000 copies/mL >24 weeks after ART initiation. Drug resistance testing was performed for pretreatment (baseline) and failure samples from participants with virologic failure. Results: HIV genotyping results were obtained for 211/249 participants (128 early ART arm and 83 delayed ART arm) with virologic failure. Drug resistance was detected in 4.7% of participants at baseline; 35.5% had new resistance at failure. In univariate analysis, the frequency of new resistance at failure was lower among participants in the early ART arm (compared with delayed ART arm, P = 0.06; compared with delayed ART arm with ART initiation before May 2011, P = 0.032). In multivariate analysis, higher baseline viral load (P = 0.0008) and ART regimen (efavirenz/lamivudine/zidovudine compared with other regimens, P = 0.024) were independently associated with higher risk of new resistance at failure. Conclusions: In HPTN 052, the frequency of new drug resistance at virologic failure was lower in adults with early ART initiation. The main factor associated with reduced drug resistance with early ART was lower baseline viral load.